Ethnoscience-Based Student Worksheet Development to Improve Senior High School Student Creativity - Dika Tri Andani; Abdul Gani; Andi Ulfa Tenri Pada; Hafnati Rahmatan (Postgraduate, University of Mataram, 2021)
Teaching materials that link the material with the surrounding life to foster an entrepreneurial spirit and creative thinking. One proof of its relevance is using plants as natural developers in making pancakes. The purpose of this study was to develop ethnoscience-based worksheets to determine the feasibility and creativity of students. The method used in this research is development research (R&D) using the ADDIE model. The population for this study was students of class XII IA Senior High School 2 Unggul Ali Hasjmy. The sample was selected purposively, namely 28 students. Data were collected using validation tests and creativity observation sheets. The results showed that the development of worksheets was very feasible to use with the percentage of 85.20 given by the validator. Validation of the creativity observation sheet states that 25 of the 26 items are feasible to use. Student creativity also increased with a percentage of the high category 89.00. Ethnoscience-based worksheets to increase student creativity are feasible to be used as teaching material.